2021
DOI: 10.1002/acn3.51331
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based study of head injury, cognitive function and pathological markers

Abstract: Objective To assess associations between head injury (HI) with loss of consciousness (LOC), ageing and markers of later‐life cerebral pathology; and to explore whether those effects may help explain subtle cognitive deficits in dementia‐free individuals. Methods Participants (n = 502, age = 69–71) from the 1946 British Birth Cohort underwent cognitive testing (subtests of Preclinical Alzheimer Cognitive Composite), 18F‐florbetapir Aβ‐PET and MR imaging. Measures include Aβ‐PET status, brain, hippocampal and wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Regarding sport‐related concussion research on Nf included American football, soccer, ice‐hockey, rugby and contact sports (Joseph et al, 2019; Pattinson et al, 2020). The evidence is however not yet conclusive at population level (James et al, 2021) or targeted at top professional football players (Cornali et al, 2022). A word of caution also comes from post‐mortem data which highlight the likelihood of multiple neuropathologies as source for increased body fluid Nf levels (Asken et al, 2022).…”
Section: Diseasesmentioning
confidence: 99%
“…Regarding sport‐related concussion research on Nf included American football, soccer, ice‐hockey, rugby and contact sports (Joseph et al, 2019; Pattinson et al, 2020). The evidence is however not yet conclusive at population level (James et al, 2021) or targeted at top professional football players (Cornali et al, 2022). A word of caution also comes from post‐mortem data which highlight the likelihood of multiple neuropathologies as source for increased body fluid Nf levels (Asken et al, 2022).…”
Section: Diseasesmentioning
confidence: 99%
“…85 James and colleagues (2021) also observed no associations between TBI with loss of consciousness (LOC) and amyloid status; however, TBI with LOC was associated with lower cognitive function on the digit symbol substitution test (DSST). 86 Evidence of a link between TBI with LOC and cognitive changes, but no association with amyloid deposition on PET, is somewhat contrary to the study by Asken and colleagues (2021) which found no evidence of an impact of TBI on either cognition or amyloid. 86 However, that study examined only mTBI subjects, which suggests LOC may be a better predictor of dementia-related cognitive changes than simply the presence or absence of a TBI.…”
Section: Evidence For Cortical Amyloid Depositionmentioning
confidence: 71%
“…These ROIs included measures of global amyloid status and/or burden, as well as the frontal, parietal, temporal, and occipital lobes, the corpus callosum and/or fornix, the anterior and the posterior cingulate, and the cuneus or precuneus (Table 4). [74][75][76][77][78][79][80][85][86][87][88][89][90][91][92][93][94][95] Global amyloid status and/or burden Schneider and colleagues (2019) found history of TBI to be associated with increased global cortical Florbetapir SUVRs in cognitively normal individuals. 89 Mielke and colleagues (2014) similarly observed no association between TBI and amyloid deposition in cognitively normal individuals via [ 11 C]-PiB, but amongst individuals with mild cognitive impairment (MCI), those with TBI had ~18% higher global amyloid and 5-fold higher odds of increased amyloid compared to those without TBI.…”
Section: Evidence For Cortical Amyloid Depositionmentioning
confidence: 99%
“…Notably, two recently published retrospective analyses closely simulated clinical practice. James et al reported the analysis of 98 patients with gMG with a mean follow-up period of 2.7 years (42). All patients were subjected to eculizumab therapy and had undergone prior therapy (cholinesterase inhibitors, oral corticosteroids, or other immunosuppressive treatments) at the initiation of treatment.…”
Section: Clinical Trials Of Eculizumab In Patients With Mgmentioning
confidence: 99%
“…The participants were divided into an eculizumab group and a control group. Remission was achieved in most patients, and the disease was controlled to a certain extent in each patient by week 12 of eculizumab treatment, according to the MG-ADL and quantitative myasthenia gravis (QMG) scores ( 42 ). Renato et al.…”
Section: The Development Of Eculizumabmentioning
confidence: 99%